INTERIOR METAVERSE TECHNOLOGY IMPLEMENTATION TO SUPPORT THE STANDARD OF PHARMACY SERVICES - Akhmadi, Akhmadi; Ismiranti, Athifa Sri; Pratiwi, Bhekti; Azhar, Hanif (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Pharmacy services which accessible in the community are drug store facilities such as pharmacies. Pharmacy services are more than just selling drugs; there are consultations the diseases, the redemption of prescriptions from doctors, and sharing about healthy living with the pharmacist on duty. The School of Pharmacy, Bandung Institute of Technology (SF ITB), was chosen for the case study. The vision and mission of the SF ITB Educational Pharmacy are to implement and demonstrate pharmaceutical services according to standards. However, the lack of enthusiasm from visitors hampers this to be able to consult with pharmacists. The interior metaverse technology method is expected to increase visitor enthusiasm and socialize the service standards to residents, especially future pharmacist candidates. The interior redesign of the SF ITB pharmacy is processed and combined with Virtual Reality (VR) glasses to support pharmacy interior design standards that optimise pharmacy services. The results show that interior metaverse technology received positive feedback from ITB pharmacy students and staff. The respondent’s enthusiasm for pharmaceutical service standards also increased after seeing the interior design of the pharmacy with immersive. These two results show the positive trend of metaverse technology in increasing the visualisation to gain the standart. Keyword : Interior, Virtual Reality, Metaverse, Immersive, Pharmacy